Histopathological Study of Coronary Atherosclerosis Using Special Stains and CD 34 Immunohistochemical Marker A Postmortem Study - Yasseen, Hadeel A.; Hamoudi, Salim R. (Journal of the Faculty of Medicine Baghdad, 2014)
Background: The coronary atherosclerosis received a great concern from the clinical aspect, but its pathological aspect is deficient in Iraq.  Objectives: To find a correlation between the type of the lesions that were grossly identified and their corresponding microscopical grades and Studying the effect of remodeling on preservation of the luminal area, 3) demonstrate the endothelial dysfunction in atherosclerosis.Methods: fifty cases were gathered from the Medico-legal institute in Baghdad during the period from January to July 2004.The left anterior descending (LAD), left circumflex (LCX) and right coronary artery (RCA) from 50 postmortem cases were biopsied. Cryosectioning and staining with Oil-red O stain were done for twenty five specimens, then all the cases were embedded in paraffin blocks, and stained for hematoxylin and eosin (H&E) stain, Verhoff Van Gieson (VVG), twenty cases were stained with CD34 immunohistochemical marker. Cases were graded according to the American Heart Association (AHA) classification system.Results: Seventy three per cent of grossly normal specimens were microscopically normal, while grossly flat fatty streaks correspond in 83% of cases to grade II. Raised fatty streaks were 100% grade III (intermediate lesions) and raised lesions were 100% advanced lesions (grade IV, V and VI). This study also shows that with progressive increment of plaque area, the total arterial cross-sectional area increased trying to preserve the lumen area. Endothelial dysfunction was also shown by decrease expression of CD34 immunohistochemical marker in diseased segments.Conclusions: gross inspection of the vessel is a valuable method for detection of intermediate and advanced lesion, while the differentiation of early lesion from normal vessel needs microscopical examination. Remodeling has a great role in maintaining luminal patency in the major coronary arteries. This study also demonstrates the endothelial dysfunction overlying the atheroma in spite of endothelial integrity.